Efeitos da adição de carga no treino de marcha na esteira em indivíduos com Doença de Parkinson: ensaio clínico controlado randomizado - Trigueiro, Larissa Coutinho de Lucena (2011)
Introduction: The intrinsic gait disorders in individuals with Parkinson's disease (PD) are one of the most disabling motor symptoms. Among the therapeutic approaches used in attempts to improve the motor function, especially the gait pattern of individuals, stands out the treadmill gait training associated with the addition of load. However, there are few findings that elucidate the benefits arising from such practice. Objective: To assess the effects of adding load on the treadmill gait training in individuals with PD. Material and Methods: A controlled, randomized and blinded clinical trial, was performed with a sample of 27 individuals (18 men and 9 women) with PD, randomly assigned to three experimental conditions, namely: treadmill gait training (n=9), treadmill gait training associated with addition of 5% load (n=9) and treadmill gait training associated with addition of 10% load (n=9). All volunteers were assessed, during phase on of Parkinson's medication, regarding to demographic, clinical and anthropometric (identification form) data, level of disability (Hoehn and Yahr Modified Scale), cognitive function (Mini Mental State Examination), clinical functional - in those areas activity of daily living and motor examination (Unified Parkinson's Disease Rating Scale - UPDRS) and gait cinematic analysis was performed through Qualisys Motion Capture System®. The intervention protocol consisted of gait training in a period of 4 consecutive weeks, with three weekly sessions, lasting 30 minutes each. The post-intervention assessment occurred the next day after the last training session, which was performed cinematic analysis of gait and the UPDRS. Data analysis was performed using the software Statistical Package for Social Sciences® (SPSS) 17.0. Results: The age of volunteers ranged from 41 to 75 years old (62,26 ± 9,07) and the time of clinical diagnosis of PD between 2 to 9 years (4,56 ± 2,42). There was a reduction regarding the score from motor exam domain (p=0,005), only when training with the addition of a 5% load. As for the space-time variables there was no significant difference between groups (p>0,120); however, the training with addition of 5% load presented the following changes: increase in stride length (p=0,028), in step length (p=0,006), in time balance of the most affected member (p=0,006) and reduction in support time of the referred member (p=0,007). Regarding angular variables significant differences between groups submitted to treadmill gait training without addition load and with 5% of load were observed in angle of the ankle at initial contact (p=0,019), in plantar flexion at toe-off (p=0,003) and in the maximum dorsiflexion in swing (p=0,005). While within groups, there was a reduction in amplitude of motion of the ankle (p=0,048), the only workout on the treadmill. Conclusion: The treadmill gait training with addition of 5% load proved to be a better experimental condition than the others because it provided greater gains in a number of variables (space-time and angular gait) and in the motion function, becoming a therapy capable of effectively improving the progress of individuals with PD